The education of an indigenous woman: the pursuit of truth, social justice and healthy relationships in a Coast Salish community context - Underwood, Mavis Kathleen (2018)
In 1951 British Columbia public schools opened their doors to First Nations children furthering federal government goals of assimilation. First Nations learners entered provincial public schools as a "billable commodity" while newcomers flooded British Columbia seeking opportunities in a province rich in natural resources in forests, mines, fisheries and land. Sadly the public schools' curricula contained colonization history but no curriculum to describe First Nations existence and history. Locally, there was no recognition of the existence of the Coast Salish people as distinct and prosperous Saltwater People. The indifference to the history of indigenous peoples left newcomers with gaps in their understanding of First Peoples Hostilities and resentments grew as immigration multiplied the numbers and pressure of homesteaders encroaching on traditional indigenous homelands paired with increasing intrusion and restrictions under the Indian Act and shrinking of traditional territories to small contained reserves. Graduate